Recent advances in osteoclast biology and pathological bone resorption. - Blair, H; Athanasou, N (2004)
The osteoclast is a bone-degrading polykaryon. Recent studies have clarified the differentiation of this cell and the biochemical mechanisms it uses to resorb bone. The osteoclast derives from a monocyte/macrophage precursor. Osteoclast formation requires permissive concentrations of M-CSF and is driven by contact with mesenchymal cells in bone that bear the TNF-family ligand RANKL. Osteoclast precursors express RANK, and the interaction between RANKL and RANK (which is inhibited by OPG) is the major determinant of osteoclast formation. Hormones, such as PTH/PTHrP, glucocorticoids and 1,25(OH)2D3, and humoral factors, including TNFalpha, interleukin-1, TGFss and prostaglandins, influence osteoclast formation by altering expression of these molecular factors. TNFalpha, IL-6 and IL-11 have also been shown to promote osteoclast formation by RANKL-independent processes. RANKL-dependent/independent osteoclast formation is likely to play an important role in conditions where there is pathological bone resorption such as inflammatory arthritis and malignant bone resorption. Osteoclast functional defects cause sclerotic bone disorders, many of which have recently been identified as specific genetic defects. Osteoclasts express specialized proteins including a vacuolar-type H+-ATPase that drives HCl secretion for dissolution of bone mineral. One v-ATPase component, the 116 kD V0 subunit, has several isoforms. Only one isoform, TCIRG1, is up-regulated in osteoclasts. Defects in TCIRG1 are common causes of osteopetrosis. HCl secretion is dependent on chloride channels; a chloride channel homologue, CLCN7, is another common defect in osteopetrosis. Humans who are deficient in carbonic anhydrase II or who have defects in phagocytosis also have variable defects in bone remodelling. Organic bone matrix is degraded by thiol proteinases, principally cathepsin K, and abnormalities in cathepsin K cause another sclerotic bone disorder, pycnodysostosis. Thus, bone turnover in normal subjects depends on relative expression of key cytokines, and defects in osteoclastic turnover usually reflect defects in specific ion transporters or enzymes that play essential roles in bone degradation.